THE INFLUENCE OF ANDROID-BASED INTERACTIVE LEARNING MEDIA DESIGN TO INCREASE STUDENT INTEREST AND LEARNING OUTCOMES IN HEALTH VOCATIONAL SCHOOLS - Fathul Razak (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
The purpose of paper This is For know more in regarding the Strategy for Legal Entity Universities ( PTNBH) in Increase Revenue Generating, Efficiency Economic Resources and Optimization Performance Achievements ( Privatization of Education Opportunities and Challenges ) results from discussion paper This is With see 3 ( three ) elements important in something business that is elements of Revenue Generating, Efficiency Economic Resources and Optimization Performance Achievement then college high who want independent or Legal Entity Universities ( PTN-BH) must Work in a way different with build systems , infrastructure , and mechanisms that will possible learners become more familiar and comfortable with concepts and situations that are not Certain